Promoting running as the best treatment for lower back pain in physiotherapy practice: a best practice implementation project - Jaster, Christina; Klugarová, Jitka; Królikowska, Aleksandra; Kołcz, Anna; Peričić, Tina Poklepović; Bała, Małgorzata M; Vrbová, Tereza; Becker, Roland; Prill, Robert (JBI evidence implementation, 2024)
OBJECTIVES: This project aimed to promote running as the best treatment for lower back pain (LBP) in an outpatient setting. INTRODUCTION: LBP is one of the most prevalent conditions worldwide. Sixty-two percent of all Germans experience episodes of non-specific back pain at least once a year, with one-fifth developing chronic conditions. Intervertebral disc (IVD) degeneration is a natural process, contributing to periods of acute LBP. However, the scientific literature and guidelines partially overlook the significance of water management in IVD. This implementation project sought to address this gap by educating patients about this process. Running and/or walking were chosen as general approaches for treatment rather than specific disease-related approaches. METHODS: This implementation project was conducted in an outpatient physiotherapy clinic in Brandenburg, Germany, utilizing the JBI Evidence Implementation Framework. An evidence-informed clinical audit and feedback strategy was used to measure compliance with ten audit criteria. Five physiotherapists and 20 patients took part in the audits. RESULTS: At baseline, only 20% of participating physiotherapists screened for yellow flags regarding psychological issues. However, after project implementation, this criterion scored 100% compliance. Some patients performed exercises independently, but confusion persisted regarding the choice of beneficial exercises. Patients continued running, but those who took a break due to pain expressed uncertainty about resuming. CONCLUSIONS: The project highlighted the effectiveness of collaborative efforts between patients and therapists to address the issue. The project team's conviction in action and solution strategies serves as the foundation for this collaboration. This implementation strategy provided "running" patients with the confidence to either resume or reintegrate running after an extended break. SPANISH ABSTRACT: http://links.lww.com/IJEBH/A222.
Keywords: lékařská praxe založená na důkazech; Patient Education as Topic; dospělí; Germany; Female; techniky fyzikální terapie; Adult; ženské pohlaví; běh; lidé; vzdělávání pacientů jako téma; Physical Therapy Modalities; Evidence-Based Practice; Exercise Therapy; Německo; Low Back Pain; Running; Male; lumbalgie; terapie cvičením; lidé středního věku; mužské pohlaví; Middle Aged; Humans